Healths problems in German Paralympic athletes preparing for the 2020 Tokyo Paralympic Games - Busch, A.; Kubosch, E. J.; Meidl, V.; Bretthauer, B.; Leonhart, R.; Dallmann, P.; Wrobel, N.; Hirschmüller, A. (Deutsche Zeitschrift für Sportmedizin, 2021)
Summary